Analisis Sosialisasi Perpajakan dan Pengetahuan Perpajakan Dalam Upaya Meningkatkan Kepatuhan Wajib Pajak Orang Pribadi di Kantor Pelayanan Pajak (KPP) Pratama Kupang - Fatima Putriani Magalhaes; Yohanes Demu; Siprianus G. Tefa (Asosiasi Riset Ekonomi dan Akuntansi Indonesia, 2024)
This research aims to analyze the tax outreach efforts that have been carried out and taxpayers' tax knowledge in an effort to increase individual taxpayer compliance at the Pratama Kupang Tax Service Office (KPP). This research focuses on the effectiveness of tax socialization that has been carried out, the level of tax knowledge of taxpayers and the level of compliance of individual taxpayers. The research method used is descriptive qualitative where data is collected through in-depth interviews, observation and documentation. The research results show that tax socialization and tax knowledge are interconnected and together influence the level of compliance of individual taxpayers at KPP Pratama Kupang both in terms of accuracy of reporting and tax payments.